Visual capture and the experience of having two bodies – Evidence from two different virtual reality techniques - Heydrich, Lukas; Dodds, Trevor; Aspell, Jane; Herbelin, Bruno; Buelthoff, Heinrich; Mohler, Betty; Blanke, Olaf (Frontiers in Psychology, 2013)
In neurology and psychiatry the detailed study of illusory own body perceptions has suggested close links between bodily processing and self-consciousness. One such illusory own body perception is heautoscopy where patients have the sensation of being reduplicated and to exist at two or even more locations. In previous experiments, using a video head-mounted display, self-location and self-identification were manipulated by applying conflicting visuo-tactile information. Yet the experienced singularity of the self was not affected, i.e. participants did not experience having multiple bodies or selves. In two experiments presented in this paper, we investigated self-location and self-identification while participants saw two virtual bodies (video-generated in study 1 and 3D computer generated in study 2) that were stroked either synchronously or asynchronously with their own body. In both experiments, we report that self-identification with two virtual bodies was stronger during synchronous stroking. Furthermore, in the video generated setup with synchronous stroking participants reported a greater feeling of having multiple bodies than in the control conditions. In study 1, but not in study 2, we report that self-location – measured by anterior posterior drift – was significantly shifted towards the two bodies in the synchronous condition only. Self-identification with two bodies, the sensation of having multiple bodies, and the changes in self-location show that the experienced singularity of the self can be studied experimentally. We discuss our data with respect to ownership for supernumerary hands and heautoscopy. We finally compare the effects of the video and 3D computer generated head-mounted display technology and discuss the possible benefits of using either technology to induce changes in illusory self-identification with a virtual body.